2017
DOI: 10.18632/oncotarget.15162
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative albumin to globulin ratio predicts survival in clear cell renal cell carcinoma patients

Abstract: In this retrospective analysis, we evaluated associations between albumin to globulin ratio (AGR), clinicopathological characteristics, and survival in 592 patients with localized or locally advanced clear cell renal cell carcinoma (CCRCC) prior to nephrectomy. We found that low AGR was associated with more aggressive tumor behavior; patients with low AGR had poorer overall survival (OS) and cancer-specific survival (CSS) in Kaplan-Meier survival analyses both before and after propensity score matching, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 30 publications
3
67
1
Order By: Relevance
“…As mentioned, our analyses have shown that continuous PLR is an independent predictor of OS, but not CSS. However, in a study conducted by Chen et al, categorized PLR did not reach the level of statistical significance for either OS or CSS in multivariable analysis [40].…”
Section: Platelet-lymphocyte Ratiomentioning
confidence: 85%
“…As mentioned, our analyses have shown that continuous PLR is an independent predictor of OS, but not CSS. However, in a study conducted by Chen et al, categorized PLR did not reach the level of statistical significance for either OS or CSS in multivariable analysis [40].…”
Section: Platelet-lymphocyte Ratiomentioning
confidence: 85%
“…Several studies have regarded dNLR as an inflammation marker that can reflect the severity of systematic inflammation in several cancers, such as non-small cell lung cancer, 11 colorectal cancer, 12 and breast cancer. 13 Serum albumin has been considered to have anti-inflammatory and possible immunomodulatory properties 14 ; therefore, if albumin synthesis was restricted by systematic inflammation, damage to the immune defense system of the patient could occur. 15 Moreover, previous ALB-dNLR score, Albumin-dNLR score; CRP, C-reactive protein; DAS28 score, 28-joint count Disease Activity Score; DMARDs, disease-modifying anti-rheumatic drugs; dNLR (Derived neutrophil to lymphocyte ratio), Neutrophil count to (Leukocyte-Neutrophil count) ratio; ESR, Erythrocyte sedimentation rate; NSAIDs, non-steroidal anti-inflammatory drugs; RF, rheumatoid factor.…”
Section: Discussionmentioning
confidence: 99%
“…A preclinical study indicated that serum ALB could inhibit the growth of the breast cancer cell line MCF-7 by influencing autocrine growth regulatory factors. Studies also revealed that increased ALB and AGR were independently correlated with better survival in various cancers, including breast cancer (39)(40)(41)(42)(43)(44)(45), because ALB stabilizes DNA replication, increases the expression of major histocompatibility complex (MHC) II, and activates T cells (25,40,46).…”
Section: Discussionmentioning
confidence: 99%